Charisma and disenchantment the vocation lectures - Weber, Max 1864-1920 (New York Review of Books, 2020)
"In 1919, just months before he died unexpectedly of pneumonia, the sociologist Max Weber published two lectures that he had recently delivered at the invitation of a group of students. The question the students asked Weber to address in these lectures was simple and haunting. In a modern world characterized by the division of labor, constant economic expansion, and unrelenting change, was vocation, in intellectual work or politics, still possible? Responding to the students' sense of urgency, Weber offered his clearest account of "the disenchantment of the world," as well as a seminal discussion of the place of values in the university classroom and academic research. Similarly, in his politics lecture he gave students what is undoubtedly his pithiest version of his account of the nature of political authority. Weber's attempts to rethink vocation remain as relevant and as stirring as ever."
Keywords: Weber, Max -- 1864-1920 -- Politik als Beruf; Weber, Max -- 1864-1920 -- Wissenschaft als Beruf; Science / Philosophy; Political science / Philosophy; Learning and scholarship / Philosophy